2018
DOI: 10.1101/452086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ddx3xregulates B-cell development and light chain recombination in mice

Abstract: 35Ddx3x encodes a DEAD box RNA helicase implicated in antiviral immunity and tumorigenesis. 36We find that hematopoietic Ddx3x deficiency in Vav1-Cre mice (Ddx3x) results in altered 37 leukocyte composition of secondary lymphoid tissues, including a marked reduction in mature B 38 cells. This paucity of peripheral B cells is associated with deficits in B-cell development in the 39 bone marrow, including reduced frequencies of small pre-B cells. Bone marrow chimera 40 experiments reveal a B-cell intrinsic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…DDX3X mRNA is expressed in the germinal center specifically in light zone B cells as shown by single-cell RNA-seq analyses (82) and DDX3X protein is as well present in human and murine mature B cells (47,48). Two independent studies with several different knockout mouse models showed loss of germinal center B cells upon ablation of Ddx3x expression (47,55) and a reduction of plasmablasts (55). Overall, both studies demonstrate not only that GC B cells are impaired but also show defects several other less mature B cell populations in conditionally deficient mice when Ddx3x expression is shut down with the Vav-cre or Cd19-cre deleter (47,48,55).…”
Section: The Germinal Center Reaction C-myc and Ddx3xmentioning
confidence: 84%
See 3 more Smart Citations
“…DDX3X mRNA is expressed in the germinal center specifically in light zone B cells as shown by single-cell RNA-seq analyses (82) and DDX3X protein is as well present in human and murine mature B cells (47,48). Two independent studies with several different knockout mouse models showed loss of germinal center B cells upon ablation of Ddx3x expression (47,55) and a reduction of plasmablasts (55). Overall, both studies demonstrate not only that GC B cells are impaired but also show defects several other less mature B cell populations in conditionally deficient mice when Ddx3x expression is shut down with the Vav-cre or Cd19-cre deleter (47,48,55).…”
Section: The Germinal Center Reaction C-myc and Ddx3xmentioning
confidence: 84%
“…Studies investigating a functional redundancy of both proteins showed that murine DDX3Y and murine D1Pas1, another DEAD-box RNA helicase, can rescue a loss of function of DDX3X in hamster cells (50). Moreover, several other reports have recently provided evidence for a compensatory effect of DDX3Y in DDX3X-deficient mice since male DDX3Xdeficient have different phenotypes compared to DDX3X-deficient females, notably in brain cells (51,52), hepatocytes (53), bonemarrow derived macrophages (54) and hematopoietic cells (47,55). It was even shown that neurons lacking DDX3X have a higher level of Ddx3y mRNA again indicating the existence of a malespecific compensation mechanism, and that both murine DDX3X and DDX3Y have indeed similar or almost identical functions (51,52).…”
Section: Regulation Of Ddx3y Expressionmentioning
confidence: 99%
See 2 more Smart Citations